Implementasi Pengurangan Noise Pada Citra Rontgen Paru Menggunakan Metode Filter Adaptive-Hierarchical - Esra Putri Sion Situmorang; Nelly Astuti Hasibuan; Saidi Ramadan Siregar (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2022)
Salt & Paper Noise Is A Form Of Noise That Is Used To See Black Or White Dots On An Image The Cause Is An Error Or Damage To The Pixels In The Image. X-ray or radiography is the use of ionizing rays to form the image of the object being studied on film, radiography is generally used to see objects that are not transparent, for example, the inside of the human body. X-ray images often have unclear results, because the image is taken using X-Ray rays, the x-ray results usually have a black and white color, and can be clearly seen when placed right in front of a light source. The light source only helps to see the shadow of the image, but does not improve the quality of the image and reduce noise or dots in the image. For this reason, the author intends to try to implement the X-ray results using the Adaptive-Hierarchical filter method with the aim of eliminating noise or dots in the X-ray image and clarifying the existing image shadows. With the Adaptive-Hierarchical Filter Method I Use Two Noise Detection Methods Where Is Detection For Noise In Medium And Smooth Areas Where Noise Detects In Rusal Or Salt Pixels And Paper Detects For Noise In Strong Areas Or You Can Call It Edge Detection On Noise On The Edges Using Only Pixels That Have Been Defined